KEMAMPUAN SISWA DALAM MENGAITKAN OBJEK MATEMATIKA PADA SOAL POLA BILANGAN - Amalia Tatu; Sumarno Ismail; Resmawan Resmawan; Ismail Djakaria; Kartin Usman; Dewi Rahmawati Isa (Universitas Negeri Gorontalo, 2021)
This research was conducted with the aim of knowing to what extent students' ability to relate mathematical objects to problems number patterns. The method used in this research is a quantitative description. The data collection techniques used are tests and interviews. The data analysis technique uses model miles and hiberman, namely by reducing data, presenting data, and drawing conclusions. The results showed that students' ability to relate mathematical objects to pattern problems numbers is not maximized. This is indicated by the percentage of achievements an indicator of the ability to associate mathematical objects that only reached an average of 55.26% consisting of 48.44% fact indicators, concept 45.50%, principle 63.80%, and operation 63.33%.